Strategi Pemasaran Kreatif dalam Meningkatkan Kelayakan Bisnis: Studi Kasus Siswa Pesantren Entrepreneur Global Cahaya Nubuwwah Insani Purwakarta - Astarini, RR Dyah; Roosmalina, Anita; Dizar, Shafrani; Humam, Aldo; Anindita, Mutia; Hendrizal, Hendrizal (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
The FEB-Usakti Community Service Team (PKM) conducted training on contemporary marketing strategy implementation at Islamic Entrepreneur Boarding School (IEBS) Global Cahaya Nubuwwah Insani, Purwakarta. Forty-one participants (26 females, 15 males) attended training sessions covering mentoring, skill development, social media advertisement creation, and facilitated discussions. Preparatory activities included surveys, coordination meetings, module development, and partner coordination. The PKM activities occurred on 15–16 March 2025, from 9:00 AM to 1:30 PM. Participants completed pre-test and post-test assessments to measure material comprehension. Results showed participants recognized modern marketing significance and the necessity of social media advertising. During training, participants demonstrated enthusiasm while learning to create social media advertisements. They acknowledged that social media utilization expands consumer reach, reduces operational costs, and enhances business efficiency. Participants grasped that marketing serves as the fundamental concept of business feasibility and expressed that training proved beneficial and met their expectations. Future PKM activities should build upon previous initiatives, ensuring continuity between teams and participants. The outcome includes intellectual property rights in copyright form.